Pengaruh Bioaktivator Selulolitik untuk Mempercepat Pengomposan Tandan Kosong Kelapa Sawit (Elaeis guineensis Jacq.) - Diah Nurul Aini; Hanifa Hanifa; Dessy Sari Mulfa; Tetty Marta Linda (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2021)
Oil palm plantations are very extensive in Indonesia which have produced oil palm solid waste in the form of oil palm empty fruit bunches (OPEFB, shells and fibers. Generally, OPEFB is processed into compost but has a constraint that requires a long time of three months. The solution is to provided bioactivators.  This study aims to determine variations in the amount of cellulolytic bioactivators in composting OPEFB that is 0 ml (P1), 50 ml (P2), 75 ml (P3) and 100 ml (P4). Composting is carried out at an incubation laboratory scale for 45 days. The best research results were obtained in P4 treatment with compost quality: N-total of 2.13; C-organic: 35,45 and C/N ratio 16,68 which are in accordance with SNI standards. This cellulotic bioactivator can be developed for the production of TKKS compost on a larger scale.